Misinformation, Misrepresentation, and Misuse of Human Behavioral Genetics Research - Bergman, Karl-Olof (Journal for nature conservation, 2006)
Kaplan discusses the limitations of human behavioral genetics studies, highlighting the research limitations inherent in studying humans and the narrow policy and legal applicability of results arising from behavioral genetics studies